Natural Hazards in Sao Vicente (Cabo Verde) - Martins, Bruno; Lourenço, Luciano; Monteiro, Sílvia (Journal of Environmental Geography, 2018)
São Vicente island (República de Cabo Verde) lies within the Sahelian zone and faces a number of natural hazards, of which the most significant ones are erosion and gully formation, desertification and flash flooding hazards. Based on examples, we set out to examine the main factors involved in the development of these natural hazards from a regional point of view, while simultaneously assessing the importance of anthropic action as a structural factor. The investigation of Lazareto’s gullies (located to the west of Mindelo) aimed to determine the main factors of the gullies formation. It also sought to demonstrate that the gullies’ formation is a reliable indicator of the high rates of erosion on a regional scale. The approach to the desertification hazards was based on farmers’ perception related to the evolution of agricultural production, strategies to mitigate drought and desertification issues, consequences and future prospects based on a set of interviews conducted in Ribeira da Vinha. Finally, the intense rainfall event that occurred on August 26, 2008 was analysed to identify the main vulnerability factors of the city in light of the flash flood hazard.